The Interaction of Urolithins and its Metabolites with Cholinesterase and the Oxidative Stress Mechanisms - Noshadi, Bahareh (Doğu Akdeniz Üniversitesi, 2020)
The beneficial effects of ellagitannin rich diet has been known for the treatment of Alzheimer Disease. Regarding the lack of bioavailability of ellagitannins and their in gastrointestinal tract to urolithins, these biological effects are attributed to the bioavailable urolithin derivatives. Urolithins are benzo[c]chromen-6-one derivatives, with hydroxyl substitutions. Within this study, we have synthesized the major urolithins, their methyl ether metabolites, concomitant to some synthetic analogues. The potential of compounds to inhibit cholinesterases, monoamine oxidase-B, cyclooxygenase enzymes were investigated. Besides, their antioxidant activities were also evaluated in DPPH antioxidant assay system. The results for the first time described a structure activity relationship in some of the biological activities of urolithins. Furthermore, a mechanistic approach for the action of ellagitannin rich food for the treatment and preventation from Alzheimer Disease was also provided. Keywords: alzheimer disease, urolithin, benzo[c]chromen-6-one, cholinesterases, cyclooxygenase enzymes, monoamine oxidase-B, DPPH antioxidant, urolithin.

ÖZ: Alzheimer Hastalığı tedavisinde ellagitannin yönünden zengin besinlerin faydası uzun zamandır bilinmektedir. Ellagitanninlerin biyoyararlanımlarının olmaması ve mide-barsak kanalında ürolitinlere dönüşümü sebebiyle ellagitanninlerin biyolojik aktiviteleri ürolitinlerle ilişkilendirilmektedir. Ürolitinler hidroksil sübstitüe benzao[c]kromen-6-on türevleridir. Bu çalışmada major ürolitinleri, metil eter metabolitleri ile bazı sentezledik analoglarını sentez ettik. Bu bileşiklerin kolinesteraz, MAO-B, siklooksijenaz enzimlerini inhibe etme potansiyellerini araştırdık. Bunun yanında, DPPH antioksidan deney sisteminde antioksidan etkilerini de inceledik. Sonuçlar, ilk kez ürolitinlerin bazı biyolojik etkilerinin yapı-aktivite ilişkisini açıklamıştır. Ayrıca, ellagitannin yönünden zengin besinlerin alzheimer hastalığı tedavisindeki ve önlenmesindeki etkilerine yönelik mekanistik bir yaklaşım da ortaya konmuştur. Anahtar Kelimeler: alzheimer hastalığı, ellagitannin, benzao[c]kromen-6-on, kolinesteraz, siklooksijenaz, DPPH antioksidan, MAO-B, urolithin.
Doctor of Philosophy in Chemistry. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2020. Supervisor: Co-Supervisor: Prof. Dr. Mustafa Gazi, Supervisor: Assoc. Prof. Dr. Hayrettin Ozan Gülcan.
Keywords: Alzheimer disease; urolithin; benzo[c]chromen-6-one; cholinesterases; cyclooxygenase enzymes; monoamine oxidase-B; DPPH antioxidant; urolithin